Modelamento matemático para otimização de perfuração em seções de pré-pal: um foco em operações no oceano Atlântico sul - Nascimento, Andreas [UNESP] (2016)
Pre-salt basins and their exploration have become more and more frequently mentioned over the years, not just for their potential reserves, but also for the implicit challenges in terms of operations to face in order to make these fields commercially viable. Several research efforts aimed at addressing these related barriers, in which drilling optimization and efficiency are presented as a considerably complex area. The problematic is concentrated in the low drillability and in the high cost involved when drilling the pre-salt carbonates. The outcome of this research is based in studies performed on top of eight pre-salt wells, addressing drilling operational time savings referenced by benchmarks and drilling mechanics parameters choosiness. The studies were based on simulations performed with penetration rate (ROP) modeling combined with specific energy (SE). The Bourgoyne Jr. and Young Jr. (1974) ROP model was used given the high errors presented for the other models, higher than 40% and, in terms of SE, the formulations from Teale (1965) and Pessier et al. (1992) were used. All these classic literature are still present in the industry and the software Oracle Crystal Ball was used as a supportive tool for the simulations. This research yielded four important results: 1) the polycrystalline diamond compact (PDC) is the most suitable drill-bit choice for pre-salt, presenting the lowest teeth-cutters wear rate, 0.28 [%/ m]; 2) the possible spare in operational time encountered for the pre-salt operations represent a saving of approximately 13,747,550.00 [USD] for the analyzed pre-salt wells; 3) the final mathematical model developed, after the adjustments for pre-salt, foresee an improvement dropping the relative error from 36.52% to 23.12% in terms of comparing the calculated and modeled ROP with the field measured ROP; 4) the final model yielded from the combination of the ROP and SE formulations is the most adequate to be used in the industry, since it was possible to foresee an improvement by dropping the relative error even more, from 23.12% to 21.2%.